IMPLEMENTASI TEKNOLOGI GAME DRESS-UP BERBASIS ANDROID - Yunda Heningtyas; Astria Hijriani; Rahmi Permata Hati; Akmal Junaidi (Lambung Mangkurat University, 2022)
Fashion is a way for women to express themselves in social life. Women who know their body shape can determine the appropriate clothes to enhance the beauty of their appearance. However, not all women understand their body shape. Women have five types of body shapes with their respective advantages and disadvantages. Dress-Up Game is a simulation game that explains the characteristics of a woman's body shape with 2-dimensional images. This game also provides a model of clothing that suits body shape. The dress-Up game is made using the Multimedia Development Life Cycle (MDLC) method and is operated on the Android platform. This Dress-Up game aims to help women understand clothes that suit their body shape.Keywords: android, body shape, Dress-Up, game simulationFashion merupakan salah satu cara wanita untuk mengekspresikan diri dalam kehidupan sosial. Wanita yang mengetahui bentuk tubuhnya dapat menentukan pakaian yang sesuai sehingga meningkatkan keindahan dari penampilannya, Namun, tidak semua wanita memahami bentuk tubuh mereka. Wanita memiliki 5 jenis bentuk tubuh dengan kelebihan dan kekurangannya masing-masing. Game Dress-Up merupakan game simulasi yang menjelaskan ciri-ciri bentuk tubuh wanita disertai gambar 2 dimensi. Game ini juga menyediakan model pakaian yang sesuai dengan bentuk tubuh. Game Dress-Up dibuat menggunakan metode Multimedia Development Life Cycle (MDLC) dan dioperasikan platform Android. Game Dress-Up ini bertujuan untuk membantu wanita dalam memahami pakaian yang sesuai dengan bentuk tubuh.Kata kunci: android, bentuk tubuh, Dress-Up, game simulasi